2021
DOI: 10.3390/antibiotics10020190
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Determinants and Multidrug Resistance of Escherichia coli Isolated from Migratory Birds

Abstract: Migratory birds are carriers of multidrug resistant pathogenic Escherichia coli. However, their roles in the dissemination of these resistant pathogens are still being neglected in Bangladesh. The present study was therefore carried out to detect multidrug resistant E. coli. In addition, these isolates were also screened for the presence of avian pathogenic E. coli (APEC)-associated virulence genes. A total of 66 fecal matter samples of migratory birds were screened. E. coli were isolated and identified by cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 62 publications
4
53
0
Order By: Relevance
“…The bovine strains were resistant to at least four classes of antibiotics, the swine strains expressed resistance to at least three antimicrobial classes and the magpie isolate displayed reduced susceptibility to five classes. Recent studies have confirmed the presence of MDR ESBL-producing E. coli among cattle [38,39], pigs [39,40], and wild birds [41,42], in various regions.…”
Section: Discussionmentioning
confidence: 91%
“…The bovine strains were resistant to at least four classes of antibiotics, the swine strains expressed resistance to at least three antimicrobial classes and the magpie isolate displayed reduced susceptibility to five classes. Recent studies have confirmed the presence of MDR ESBL-producing E. coli among cattle [38,39], pigs [39,40], and wild birds [41,42], in various regions.…”
Section: Discussionmentioning
confidence: 91%
“…E. coli strains used in this study were obtained in our previous study on migratory birds [ 19 ]. Original detection and isolation of these E. coli strains were done following culture on eosin methylene blue agar (HiMedia, India) plates, grams staining, biochemical tests (catalase test, coagulase test, sugar fermentation tests, methyl red test, Voges–Proskauer test, and indole test), and PCR targeting malB gene [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic resistance is currently a serious problem worldwide that threatens human, animal and environmental health [ 1 ]. If the situation remains unmanaged by 2050, higher human mortalities, severe economic losses and a significant drop in livestock production are expected [ 2 ].…”
Section: Introductionmentioning
confidence: 99%